Green Branding and Maritime Service Marketing: How Environmental Certification Shapes Customer Loyalty and Competitive Positioning Among Global Shipping Companies - Tata Heru Prabawa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The maritime industry is under increasing pressure to integrate environmental sustainability practices into its commercial operations, reshaping the way shipping companies position themselves in global markets. This study explores the role of environmental certification systems—such as Green Award, ISO 14001, and IMO environmental compliance frameworks—as green branding tools that impact customer loyalty and competitive positioning within the global shipping industry. Utilizing a qualitative research approach, the study employs thematic analysis of in-depth interviews conducted with a diverse range of maritime industry stakeholders, including port operators, freight forwarders, shipping lines, and regulatory bodies. The findings highlight that environmental certification enhances brand credibility, fosters stronger business-to-business (B2B) customer retention, and enables competitive differentiation in increasingly eco-conscious markets. By bridging the gap between environmental compliance and commercial performance, the study makes a significant contribution to maritime marketing literature, illustrating how green branding strategies can serve as a key driver of business success in the context of the global shipping industry's sustainability-driven transformation.